Tapered multimode fiber sensor for salinity detection - Mustapa, Mohd Azmir; Abu Bakar, Muhammad Hafiz; Amir Hamzah, Amir Syahir; Mahdi, Mohd Adzir (IEEE, 2014)
A tapered multimode fiber as a salinity sensor was demonstrated. The sensitivity of the sensor could be enhanced by tapering the multimode fiber to a 10μm diameter size and 50mm of waist length. The tapered multimode fiber sensor was tested with the different concentration of sodium chloride (NaCl) which is diluted in the distilled water. The tapered multimode fiber sensor (TMFS) is easy to fabricate, compact, and simple. The sensitivity of the sensor achieved 0.1705 a.u/M. The findings demonstrated the capability of TMFS for salinity sensing and its potential application for detection of chemical sample.